ANTHROPOMETRIC CHARACTERISTICS AND PHYSICAL FITNESS LEVEL IN RELATION TO BODY WEIGHT STATUS IN SIX-YEAR-OLD MACEDONIAN CHILDREN - Emini, Bejtulla; Saiti, Agon; Gontarev, Seryozha; Baftiu, Sedat; Cemena, Yllka (University Ss. Cyril and Methodius in Skopje, 2022)
Background: Macedonian children show the same tendencies in excess weight and obesity as children in developed countries a decade ago. Childhood excess weight is associated with chronic diseases, early mortality in adulthood, and psycho-social effects with lifelong consequences. The purpose of this study is to describe the anthropometric and physical fitness characteristics of Macedonian children and to examine whether weight status influences children’s performance on fitness tests. Methods: A total of 353 preschool children (154 boys; 199 girls; 6.73 ± 0.48 years) participated in our study. Anthropometry (weight, height, body mass index –BMI, WC, and body composition) and fitness tests (sit and reach test, handgrip strength test, standing broad jump test, sit-ups 30 sec., shuttle run 4 х 10 meters and 20 m shuttle run test) were assessed by trained physical education teachers, respectively. International cut-off points were used to categorize children into normal weight, overweight or obese categories. Data were analyzed using descriptive statistics, analysis of variance, and analysis of covariance (ANCOVA) with age as a confounder. Results: The percentage of overweight and obese children, classified according to the BMI (Cole et al.), is equal to 34% of the Macedonian children of the same age. Significant differences were discovered in the anthropometry and fitness tests between boys and girls. Boys who were classified as overweight/obese show poorer results in the following fitness tests: standing long jump, sit-ups for 30 seconds, running 20 meters with a progressive increase in speed (sections passed) and maximal oxygen uptake, and better results in the fitness test handgrip strength. Girls classified as overweight/obese show poorer results in the following fitness tests: standing broad jump, sit-ups 30 seconds, shuttle run 4 x 10 meters, running 20 meters with a progressive increase in speed (sections passed) and maximal oxygen uptake and better results in the fitness tests handgrip strength and sit and reach. Conclusions: Health-enhancing physical fitness of young children is negatively affected by excess weight and obesity, and intervention strategies are recommended to improve the quality of life of such children but also to prevent early mortality during adulthood.